Inhibition of Hypoxia‐Induced Gene Transcription by Substituted Pyrazolyl Oxadiazoles: Initial Lead Generation and Structure–Activity Relationships. Issue 1 (27th November 2013) - Härter, Michael; Thierauch, Karl‐Heinz; Boyer, Stephen; Bhargava, Ajay; Ellinghaus, Peter; Beck, Hartmut; Greschat‐Schade, Susanne; Hess‐Stumpp, Holger; Unterschemmann, Kerstin
Abstract The transcription factors hypoxia‐inducible factor‐1 and ‐2 (HIF‐1 and HIF‐2) orchestrate a multitude of processes that allow tumor cells to survive under conditions of low oxygen and nutrients, and that lead to resistance to some apoptotic pathways and facilitate invasion and metastasis. Therefore, inhibition of transactivation by HIF has become an attractive target in cancer research. Herein we present the results of a cell‐based screening approach that led to the discovery of substituted 1H‐pyrazole‐3‐carboxamides. Chemical optimization of the hit class with respect to potency and metabolic stability is described; it resulted in novel 5‐(1H‐pyrazol‐3‐yl)‐1, 2, 4‐oxadiazoles that inhibit the hypoxia‐induced accumulation of HIF‐1α and HIF‐2α. The HIF inhibitory potency in the screening cell system was improved from IC50 190 to 0.7 nM, and significant parts of the SAR are disclosed. For a key compound, the ability to suppress the hypoxia‐induced expression of HIF target genes was studied in A549 human lung adenocarcinoma cells. The same compound shows a favorable pharmacokinetic profile in rats after i.v. and p.o. administration.